women age and embryo implantation following intracytoplasmic sperminjection and embryo transfer in infertile patients - AL- barzanchi, mundhir T.; AL-Anssari, Saeeda M.; khunda, Sarmad S.; Allow, Ahmed K.; kanan, Zuhair K. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: